A Case Study of Deep Vein Thrombosis of the Right Internal Jugular Vein in a Healthy 21-Year-Old Male - Javier Corral; Geri Villanueva (Case Reports in Hematology)
We are reporting a case of a healthy 21-year-old male, with no significant past medical history, who was found to have an incidental nonocclusive deep vein thrombosis in the right internal jugular vein detected on a head MRI previously ordered for work-up of headaches. A follow-up upper extremity venous Doppler ultrasound confirmed the presence of a partially occlusive deep vein thrombosis in the right jugular vein. The case presented is unique for the reason that the patient is young and has no prior risk factor, personal or familial, for venous thrombosis except for associated polycythemia on clinical presentation.